1998
DOI: 10.2169/internalmedicine.37.449
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Splenic Sarcoidosis Evaluated by Multiple Imaging Modalities.

Abstract: Wepresent a case of hepatosplenic sarcoidosis. A 51-year-old Japanese male, who was diagnosed to have sarcoidosis 4 years previously, was presented to our hospital because of dry cough and anorexia with weight loss. He had tender hepatosplenomegaly. A dynamic abdominal computed tomography (CT) revealed multiple small low-density areas in both liver and spleen, as well as in magnetic resonance imaging (MRI). The laparoscopic photographs showed many small whitish nodules surfacing on the liver and several tumoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 17 publications
1
23
1
2
Order By: Relevance
“…20 In our patient, multiple nodular lesions, measuring 5 to 10 mm in diameter, were detected in the liver and spleen by CT and MRI. The capacities and limitations of the various imaging modalities to detect the sarcoid granulomas in our patients seem to be comparable to those in previous reports, although case reports of splenohepatic sarcoidosis detectable by MRI are limited, [21][22][23] and the authors of these reports have suggested that, on MRI, hepatic sarcoidosis is more difficult to detect than splenic lesions. [21][22][23] To summarize, we assumed that our patient had developed liver cirrhosis caused mainly by hepatic sarcoidosis, rather than by chronic hepatitis C, based on the following findings.…”
Section: Discussionsupporting
confidence: 87%
“…20 In our patient, multiple nodular lesions, measuring 5 to 10 mm in diameter, were detected in the liver and spleen by CT and MRI. The capacities and limitations of the various imaging modalities to detect the sarcoid granulomas in our patients seem to be comparable to those in previous reports, although case reports of splenohepatic sarcoidosis detectable by MRI are limited, [21][22][23] and the authors of these reports have suggested that, on MRI, hepatic sarcoidosis is more difficult to detect than splenic lesions. [21][22][23] To summarize, we assumed that our patient had developed liver cirrhosis caused mainly by hepatic sarcoidosis, rather than by chronic hepatitis C, based on the following findings.…”
Section: Discussionsupporting
confidence: 87%
“…The organ is usually homogeneous, but multiple low-attenuating nodular lesions are occasionally noted and easily mistaken for lymphoma, metastases or infections [13,15,19]. Isolated or predominant hepatic nodular disease is less common than spleen impairement [2,5,13]. Besides spleen involvement, our patient presented also a hepatic nodule.…”
Section: Discussionmentioning
confidence: 65%
“…The diagnosis of sarcoidosis could be more complicated especially if abdominal sarcoidosis represents the exclusive involvement without systemic disease [3,6,9]. Usually, extrapulmonary disease occurs in the context of more extensive chest disease [13,14,15] (greatest splenic dimension >14 cm) is the most common splenic manifestation [19,20]. The organ is usually homogeneous, but multiple low-attenuating nodular lesions are occasionally noted and easily mistaken for lymphoma, metastases or infections [13,15,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La TDM révèle les lésions hépatiques dans 5% des cas et celles de la rate dans 15% des cas [24] ; l'IRM est plus performante surtout pour les lésions spléniques [25].…”
Section: Discussionunclassified